Protocols for Determination of Coefficient of Transpiration (Tµ) Using a New Innovative Instrument Rhythmometer Version 2 - Sanjukta Badhai; Aishwarya Khamari; Akshya Kumar Mishra; Himansu Sekhara Mohapatra (International Journal for Research in Applied Sciences and Biotechnology, 2021)
Transpiration is a physiological process by which aerial parts of plants release water in form of vapour. It is affected by many environmental factors like temperature, light, humidity, etc. In this present work, we propose a new protocol for the determination of the Coefficient of Transpiration (Tµ) which is useful for the determination of trends of transpiration concerning different climatic factors. For determination of the Coefficient of Transpiration (Tµ) can achieve by using a new innovative instrument Rhythmometer Version-2 (Fig-1) which was developed by two authors Aishwarya Khamari and Akshya Ku. Mishra in 2021. Rhythmometer (PEG) is an analytical instrument used to measure plant rhythm concerning its electrical conductivity. This instrument measures plant rhythm as well as detects several environmental parameters. In this study, it was found that the Coefficient of Transpiration was maximum in wind, moderate in sunlight, and minimum in shade and it varies with environmental factors like temperature, light intensity, wind speed, etc. Rhythmometer Version 2 not only helpful in the detection of rhythm and plant physiological processes but also detection of several environmental parameters Therefore we called it a portable all in one lab for plant physiology and phytoecology.